EFFECTIVE DEPTH OF SOIL COMPACTION UNDER A CONTROLLED COMPACTIVE EFFORT AT LABORATORY SCALE - Tascon, Andres (My University, 2011)
Embankment construction specifications in the State of Wisconsin indicate that compaction lifts cannot be thicker than 20 cm. This specification was established several years ago based on field experience when compactors were lighter and smaller than the equipment used today. Lift thickness may be increased to save construction time and cost when heavier and larger compaction equipment is used. In this research effort, the possibility of increasing lift thickness specifications in the construction industry without compromising the embankment stability is explored by developing a methodology to evaluate engineering properties of compacted soils. A laboratory soil compaction test was designed to compact soil under controlled compactive efforts while monitoring mechanical soil properties before, during and after compaction. The soil underwent eight compaction passes. The soil properties were monitored using techniques including nuclear density gauge (NDG), soil stiffness gauge (SSG), dynamic cone penetrometer (DCP), P-wave velocity tests, and MEMS-accelerometers rotations. Soil density, stiffness, shear strength, and deformation profiles were thus measured as a function of the compactive effort, soil type, water content, and lift thickness. Thicker lifts results in greater soil surface displacement but less volume change and less uniform compaction than thin lifts. Furthermore, thin lifts undergo larger strains and yield greater stiffnesses than thick lifts. A comparison of the laboratory tests performed in this study with a real soil compaction monitoring experiment shows that, despite the differences in scale, density in thick lifts decreases with depth, and shows regions of low density at the bottom of the lift. Soils with larger shear strength results when are compacted closer of the optimum water content. Analysis of the stiffness measurements shows that the use of the SSG in embankment construction using thin lift should consider the influence of the stiffness ratio between the lift and the underlying layer. The effective depth of influence of the compactor used in this laboratory study reached about 15 cm; where, as for field operations using a compactive force that is 22 times larger, the influence reaches 30 to 40 cm.